Unveiling the interfacial configuration in diamond/Cu composites by using statistical analysis of metallized diamond surface. (15th July 2018) - Zhang, Hongdi; Zhang, Jingjing; Liu, Yue; Zhang, Fan; Fan, Tongxiang; Zhang, Di
Abstract: Interfacial debonding is detrimental for the properties of diamond/Cu composites, which can be solved by diamond surface metallization with active element Cr. Using microstructure characterization and statistical investigation, we find that the diamond surface metallization undergoes dispersed growth, preferred growth, complete metallization and preferred cleavage. The preferred carbide growth on 100 surfaces and preferred carbide cleavage on 111 surfaces result from the different surface configurations. Furthermore, an amorphous carbon layer generates at diamond (111) /carbide interface for the structure transformation. Interfacial bonding between diamond and Cu is realized via reaction bonding at diamond/carbide interface and diffusion bonding at carbide/Cu interface. Graphical abstract: Unlabelled Image